Determinasi profitabilitas bank: Pengaruh rasio aktivitas dan efisiensi operasional dengan risiko kredit sebagai variabel intervening - Suchi Avita Rici; Putri Nadia; Resyelly Viona (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study aims to analyse the effects of activity ratios and operational efficiency on profitability, with credit risk serving as an intervening variable for banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach was employed using secondary data obtained from the companies’ annual financial statements. The sample was selected through purposive sampling, resulting in 26 banking companies with a total of 130 observations. Data were analysed using multiple linear regression and path analysis with the assistance of IBM SPSS Statistics 26. The findings indicate that the activity ratio does not have a significant effect on credit risk, while operational efficiency significantly affects it. In addition, activity ratios, operational efficiency, and credit risk were found to have significant effects on profitability. The results of the path analysis reveal that credit risk is unable to mediate the relationship between activity ratios and profitability, as well as between operational efficiency and profitability. Effective asset utilisation and operational efficiency, rather than the credit risk mechanism, have a stronger influence on banking profitability improvements. Based on these findings, banking institutions should optimise operational performance and asset management to sustainably enhance profitability.